Are UK Policies and Practices for Regulated Donor Insemination Forcing Women to Find Unregulated Sperm Donors Online? A Perspective on the Available Evidence - Taylor, Francesca; Turner-Moore, Rhys; Pacey, Allan; Jones, Georgina Louise (Frontiers in Global Women's Health, 2022)
In recent years, there has been an increase in women obtaining donor sperm via unregulated websites and social media. In this article, we bring together the disparate evidence in this emerging field to consider whether restrictive UK policies and practices for regulated clinical donor insemination (DI) are a potential explanation for the growing use of the currently unregulated, online route to donor insemination. To this end, we examine the nature of the National Institute for Health and Care Excellence (NICE) guidelines, recent data provided by the Human Fertilisation and Embryology Authority (HFEA), and prior research on who uses online sperm donation and their reasons for doing so. In addition, we highlight why this issue is important by outlining some of the benefits and drawbacks of the unregulated route. We argue that, whilst there are many factors driving the unregulated route to DI, restrictive UK policies and practices for regulated DI might be one of these. We conclude that turning our attention to structural barriers, such as regulated DI policies and practices, is necessary to produce more definitive evidence of this potential issue, and that adopting a Reproductive Justice framework could lead to more equitable provision of regulated DI services.